CO2 laser cutting performance on ultra high strength steel (UHSS) - M. Tahir, A. F.; Rashid, A. R.; Sariff, N. E.; A. Rahim, E. (Springer, 2020)
Evolution of a new breed steel, Ultra High Strength Steel (UHSS), has been adapted by the automotive industry after being used for heavy trucks. Higher tensile strength and improved mechanical properties of UHSS are the main reason for its selection particularly in Body In White (BIW) construction at critical chassis area. Laser cutting process is noted as the final trimming method for this harden material as die pressing resulted as an ineffective process. UHSS cutting performance using CO2 laser with variation on laser power, cutting speed, assist gas type and assist gas pressure was determined to identify the effect of these parameters on the cutting quality. Cutting quality assessment was carried out according to EN ISO 9013 standard where kerf width, perpendicularity and microhardness were evaluated based on parameters set at 1.7 mm thickness of 22MnB5 UHSS boron steel. The quality of these cuttings was evaluated as the results show that thermal exposure dependent on energy density and gas type reflect the outcome where higher thermal exposure introduced bigger kerf with better perpendicularity. It was also found that isothermal effects such as Heat Affected Zone (HAZ) and martensitic transformation were also clearly visible since nitrogen produced a better cutting quality and material integrity consumption at the cutting edge.